Quasi-Lagrangian Measurements of Nitric Acid Trihydrate Formation Over Antarctica - Ward, S. M.; Deshler, Terry; Hertzog, A. (Journal of Geophysical Research: Atmospheres, 2014)
©2013. The Authors. In 2010, the joint French-United States Concordiasi project released 19 long-duration superpressure balloons from McMurdo Station, Antarctica. Four of these balloons carried a gondola with particle counters and temperature sensors to measure polar stratospheric clouds. One gondola spent 5 days at stable temperatures between equilibrium temperatures for nitric acid trihydrate (NAT) and for supercooled ternary solution droplets. Sporadic particles with radii between 0.46 μm and 4.5 μm were measured in a small fraction of the measurements. At these times the corresponding size distributions and total particle volumes were consistent with NAT. Although the fraction of these observations was less than 3%, their frequency increased with time over the 5 days. From this frequency the NAT nucleation rate at 3°C below T NAT was estimated to be 2 × 10-4 m-3 s-1 ± 60% for these late winter austral NAT observations at a potential temperature of 410-415 K. Interspersed with these measurements of polar stratospheric cloud particles consistent with NAT were many more measurements of particles consistent with background stratospheric aerosol indicating that the polar stratospheric clouds sampled were highly discontinuous. Key points: Quasi-Lagrangian measurements of polar stratospheric cloud particles Balloon-borne measurements of nitric acid trihydrate formation.